Pengaruh Beban Kerja Perawat Terhadap Respon Time Dan Kepuasan Pasien Instalasi Rawat Jalan Di Rumah Sakit X - Raafika Studiviani Binuko; Nida Faradisa (Jurnal Infokes, 2022)
Nurses are the primary needs of hospitals and almost all hospital services. The outpatient nurse must take direct action against the patient. A large number of outpatients every day makes the workload increase. The existence of speed and accuracy in providing services to outpatients is an indicator of outpatient satisfaction. The purpose of this study was to determine the effect of the nurse's workload on response time and patient satisfaction in the outpatient installation at Hospital X. The method used in this study was analytic survey research with a cross-sectional study approach. The data processing is carried out in this study using multiple linear regression analysis between the variables of nurse workload, response time, and patient satisfaction. The results of the linearity test show that the value of Sig. In the line Deviation from Linearity is 0.793, meaning that the relationship between the Response Time and Nurse Burden variables is linear. While the line Deviation from Linearity is 0.990, meaning that the relationship between the variables of Patient Satisfaction and Nurse Burden is linear.